Critical Approaches to GIS and Spatial Mapping in Indonesia Forest Management and Conservation - Sidiq, Asrul (Forest and Society, 2021)
The conventional Geographic Information Systems (GIS) and spatial mapping techniques fail to understand a spatially complex forest area. This is because forest landscapes cannot be easily mapped into a two-dimensional map, which is usually used in spatial planning. In addition, planning maps are the fundamental factors of land grabbing issues. To solve this problem, counter-mapping arises at the local level as a tool to overcome the problem of land grabbing in forest areas in Indonesia. Counter mapping is defined here as part of a broader term under participatory mapping or citizen mapping. However, counter-mapping also faces critiques in terms of different epistemological and socio-economic-political conditions at the local level. This article elaborates the use of GIS and spatial mapping methods within a 'critical' social science approach based on literature review and field experiences. This article also aims to analyze counter-mapping as a ‘tool’ to solve the forest land-use problem, which can contribute to the choice of policy instruments in forest management and conservation in Indonesia.